Position-Keeping Method for Unmanned Sailboats Based on NMPC Maximum Speed and Heading Control - Kai Liu; Jiancheng Yu; Wentao Zhao; Zhaoyang Sun (Journal of Marine Science and Engineering)
This study examines the position-keeping control for unmanned sailboats. First, the maximum speed and heading joint control, based on nonlinear model predictive control, is proposed as the underlying control for maintaining position. On this basis, four position-keeping strategies are proposed: the straight-line trajectory strategy; the circular surround strategy; the square surround strategy, with the diagonal-to-wind angle near the expected position set to half the navigation dead zone angle; and the square surround strategy, with the diagonal-to-wind angle near the predicted position set to zero. Subsequently, simulation and hierarchical analyses were conducted to assess the effectiveness of these strategies. According to the simulation results, the average error of the straight-line trajectory strategy is less than 6.5 m, the average error of the circular surround strategy is less than 8.9 m, and the minimum error of the square surround strategy is less than 7.7 m. Considering the sail and rudder travel as an important indicator, the square surround scheme, with the angle between the diagonal near the desired position and the wind direction being, zero is the optimal strategy. Considering the position-keeping error as an important indicator, the straight-line trajectory strategy is the optimal strategy.